Prediksi Tingkat Kompetensi Profesional Pendidik Menggunakan Sistem Inferensi Fuzzy Metode Tsukamoto - Tito Pinandita; Ahmad Ahmad (JUITA : Jurnal Informatika, 2012)
The competence of a teacher is absolutely necessary to demonstrate the quality of teachers in the exercise of his profession. These competencies will be realized in the form of mastery of the knowledge and professionalism. Professional competence is one of competence as set forth in UUGD 2005 that has several components. In this study applied fuzzy inference system Tsukamoto method to predict the level of teachers’s proffesional competence. Expected with this system, the level of professional competence of teachers can be predicted by entering the scores from professional competencies supporting components